The Effect of Financial Performance toward Profit-Sharing Rate on Mudharabah Deposit of Sharia Banking in Indonesia - Sudarsono, Heri; Saputri, Miranti Aprilia (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2018)
Abstract This study aims to determine the effect of financial performance in the form of Return On Assets (ROA), Operational Expense to Operating Income (OER), Finance to Deposits Ratio (FDR), Non Performing Finance (NPF), and Interest Rate to profit-sharing rate on mudharabah deposit of Sharia banking in Indonesia period 2011.1 to 2017.10. Data analysis method used is Auto-Regressive Distributed Lag (ARDL) which can analyze the relation between independent variable to dependent variable in long term and short term. The results of data analysis show that in the short term ROA and OER variable negatively affect the profit-sharing rate mudharabah deposits. While the variable of FDR and Interest rate have positive effect to profit-sharing rate of mudharabah deposit, on the other hand NPF variable does not affect to profit-sharing level of mudharabah deposit. Meanwhile in the long run the variable of FDR and OER have negative effect, the variable of Interest rate has positive effect. Meanwhile, the ROA and NPF variables do not affect the profit-sharing of mudharabah depositsAbstrak Penelitian ini bertujuan untuk mengetahui pengaruh kinerja keuangan berupa Return On Asset (ROA), Biaya Operasional terhadap Pendapatan Operasional (BOPO), Finance to Deposits Ratio (FDR), Non Performing Finance (NPF), dan Suku Bunga terhadap tingkat bagi hasil deposito mudharabah pada perbankan syariah di Indonesia periode tahun 2011.1 sampai 2017.10. Metode analisis data yang digunakan adalah Auto-Regressive Distributed Lag (ARDL) yang dapat menganalisa keterkaitan antara variabel independen terhadap variabel dependen dalam jangka panjang dan jangka pendek. Hasil analisis data menunjukkan bahwa dalam jangka pendek variabel ROA dan BOPO berpengaruh negatif terhadap tingkat bagi hasil deposito mudharabah. Sedangkan variabel FDR dan Suku Bunga berpengaruh positif terhadap tingkat bagi hasil deposito mudharabah, dilain pihak variabel NPF tidak berpengaruh terhadap tingkat bagi hasil deposito mudharabah. Dan dalam jangka panjang variabel FDR dan BOPO berpengaruh negatif, variabel Suku Bunga berpengaruh positif. Sementara itu, variabel ROA dan NPF masing-masing tidak berpengaruh terhadap tingkat bagi hasil deposito mudharabah